Oral 5-ASA Versus Prednisone in Short Term Treatment of Crohn's Disease: A Multicentre Controlled Trial. (1st November 1990) - Martin, F; Sutherland, L; Beck, IT; Anderson, AH; Williams, CN; Saibel, F; Barrowman, J; Lemire, S
Abstract : A multicencre randomized controlled trial was designed to compare the efficacy and safety of Eudragit-L coated oral 5-aminosalicylic acid (5-ASA) (Salofalk; lnterfalk) 3 g per day to a 'standard' oral prednisone therapeutic regimen in a 12 week treatment period of uncomplicated attacks of Crohn's ileitis and ileocolitis. Fifty patients with active Crohn's disease (Crohn's disease activity index [CDAI] 200 to 450) were randomized to receive either four 250 mg Eudragit-L-100 coated 5-ASA tablets three times a day for 12 weeks or oral prednisone ( 4 mg tablets) at a sustained 40 mg per day for two weeks followed by a 4 mg/day weekly dose reduction for the 10 subsequent weeks. Efficacy was determined by changes in the calculated CDAI and, as a novel assessment, the McMaster University quality of life index at two, four, six, eight, 10 and 12 weeks. Standard blood and urine values were obtained and physician's assessment completed at each two week visit. Clinical remission was obtained in 12 of 26 patients (46%) in the prednisone group and in nine of 19 (47%) in the 5-ASA group. Treatment failure was observed in three patients in each group. All other patients improved during the treatment period. Patients on prednisone reduced their CDAI scores significantly more rapidly during the first four weeks, but the reduction and maintenance of CDAI scores were similar in both groups for the remainder of the study period. In patients with ileocolitis, prednisone was significantly better than 5-ASA. Quality of life assessment parallelled the changes in CDAI, and appear a valid index. The two therapeutic regimens appear safe and did not disclose any unexpected adverse events or side effects. No significant biological abnormalities were detected in either treatment group. In conclusion, in this small trial, it was found that Salofalk at a dose of 3 g per day appears effective treatment for active Crohn's disease, and it is proposed chat higher doses may be beneficial in more extensive disease (ileocolitis) and during the first four weeks of treatment.